One last chance - Warren, Susan May, 1966- (Alaska Air One rescue, 2024)
"As an Air One rescue swimmer, Axel Mulligan will do anything to save lives - including sacrifice his own. When wildlife researcher Flynn Turnquist enters his life, he falls hard and fast. But is she really who he thinks she is?"--